Estimating rain attenuation at THZ frequencies from historical data collected in Brasilia, DF - Morais, Lucas Vasconcelos de (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.